MATERIAL SUPPLY ESTIMATION USING THE ECONOMIC ORDER QUANTITY (EOQ) METHOD IN THE PUSKOPCUINA BUILDING PHASE I PONTIANAK CONSTRUCTION PROJECT - Pasyah, Annisa Nurul; Syahrudin, Syahrudin; Rafie, Rafie (Fakultas Teknik Universitas Tanjungpura, 2023)
Seeing the rapid development of the construction world, as part of the Indonesian economy, we need to support the growth of various facilities and infrastructure. In its growth, it must also improve its quality in all respects. In this case, material management plays an essential role in the construction process. The method chosen for this problem is the Economic Order Quantity (EOQ) method. The most economical amount of inventory can be determined by calculating the Economic Order Quantity (EOQ) method. This economical amount of stock can invest embedded in inventory materials, not excessive, so that it does not experience waste.